Clustering kinetics during natural ageing of Al-Cu based alloys with (Mg, Li) additions - Ivanov, R.; Deschamps, A.; De Geuser, F. (Acta materialia, 2018)
Room temperature solute clustering in aluminium alloys, or natural ageing, despite its industrial relevance, is still subject to debate, mostly due to its experimentally challenging nature. To better understand the complex multi-constituents’ interactions at play, we have studied ternary and quaternary subsystems based on the Al-Cu alloys, namely Al-Cu-Mg, Al-Cu-Li and Al-Cu-Li-Mg. We used a recently introduced correlative technique using small-angle neutrons and X-ray scattering (SANS and SAXS) to extract the chemically resolved kinetics of room temperature clustering in these alloys, which we completed with DSC and micro-hardness measurements. The comparison of the clustering behaviours of each subsystem allowed us to highlight the paramount role of Mg as a trigger for diffusion and clustering. Indeed, while a strong natural ageing was observed in the Al-Cu-Mg alloy, virtually none was shown for Al-Cu-Li. A very slight addition of Mg (0.4%) to this system, however, drastically changed the situation to a rapid formation of essentially Cu-rich hardening clusters, Mg only joining them later in the reaction. This diffusion enabling effect of Mg is discussed in terms of diffusion mechanism and complex interactions with the quenched-in vacancies. [Display omitted]